Efektivitas Model Pembelajaran Student Facilitator and Explaining berbantuan Game pada Mata Pelajaran Dasar-Dasar Teknik Ketenagalistrikan - Yenita, Resti Fitri; Eliza, Fivia (Jurnal Pendidikan Teknik Elektro, 2024)
This study aims to determine the effectiveness of the game-assisted Student Facilitator and Explaining (SFE) learning model in improving student learning outcomes in the subject of Fundamentals of Electrical Engineering at SMKN 1 Batipuh. This study uses an experimental method with a pre-experimental design in the form of a one-group pretest posttest. The results showed that there was a significant improvement in students' learning outcomes by using the game-assisted SFE model, showing a better understanding of electrical engineering concepts and higher critical thinking skills. In addition, the use of games as a learning medium has also been proven to make the learning process more interactive. The subjects in this study are students of class X TITL 1 at SMKN 1 Batipuh. The research instruments used are in the form of concept cards as a tool to help implement the SFE learning model, and pretest and posttest questions in objective form. Based on the average score of the posttest, it is in the high category. Therefore, the application of the Student Facilitator and Explanation learning model as a learning model in the Fundamentals of Electrical Engineering subject is said to be effective because the classical completeness value is included in the very high category and the effect size is included in the large category.